Unraveling the genetic potential of native rice (Oryza sativa L.) landraces for tolerance to early-stage submergence - Shanmugam, Aravindan; Manivelan, Kalaiarasan; Deepika, Konne; Nithishkumar, Gopal; Blessy, Viswanadhapalli; Monihasri, Raju Baskaran; Nivetha, Dhanasekar; Roshini, Arunkamaraj; Sathya, Palanivelu; Pushpa, Raman; Manimaran, Rangarajan; Subrahmaniyan, Kasirajan; et al. (Frontiers in Plant Science, 2023)
Direct Seeded Rice (DSR) is a promising alternative to the traditional puddled rice system. It has become more popular among rice growers as a result of socio-economic shift and global climate change. Although DSR offers advantages, rice plants experience greater anaerobic stress at sowing from unpredicted rainfall. Rice is unique among other cereals which is having the ability to germinate under anaerobiosis. The coleoptile of rice rapidly elongates above the water surface to obtain more oxygen and enhance vigorous seedling growth. A panel of 116 landraces and four check varieties were subjected to anaerobic stress with a water level of 10 cm for up to 15 days. Present study observed ample variation for anaerobic germination percentage (AGP) (10 to 100%) and anaerobic vigour index (AVI) (150 to 4433). Landraces Karuthakar, Poovan samba, Mattaikar, Edakkal, Manvilayan and Varappu Kudainchan were identified as genotypes tolerant to early water submergence. Shoot and root length of susceptible landraces were significantly less than those of the tolerant landraces under hypoxia, implying that landraces with longer shoots and roots had a higher survival rate. The response index substantiated this. It clearly explained that tolerant and moderately tolerant landraces possessed higher mean value for root and shoot lengths compared to the susceptible landraces. The landraces grouped under long bold category had superior AGP and AVI scores than other grain type groups. This raises the possibility that differences in kernel breadth, which is linked to grain type, could affect anaerobic germination potential. Molecular confirmation using gene-specific markers viz., DFR, TTP_G4, RM478, RM208 and RM24161 for which polymorphic information content (PIC) value ranged from 0.36 (RM478) to 0.68 (RM206) suggests that this diverse panel of landraces must be assessed further using advanced molecular tools to preciously elucidate the genetic mechanism behind this phenomenon. Tolerant landraces thus identified may become donors in breeding programmes. The introduction of these traits would contribute to development of rice varieties tolerant to anaerobic stress, resulting in sustainable yields. This solution could promote DSR system worldwide.